Spirit hermeneutics: reading scripture in light of Pentecost - Keener, Craig S. (William B. Eerdmans Publishing Company, 2016)
How do we hear the Spirit's voice in Scripture? Once we have done responsible exegesis, how may we expect the Spirit to apply the text to our lives and communities? In Spirit Hermeneutics biblical scholar Craig Keener addresses these questions, carefully articulating how the experience of the Spirit that empowered the church on the day of Pentecost can -- and should -- dynamically shape our reading of Scripture today. Keener considers what Spirit-guided interpretation means, explores implications of an epistemology of Word and Spirit for biblical hermeneutics, and shows how Scripture itself models an experiential appropriation of its message. Bridging the Word-Spirit gap between academic and experiential Christian approaches, Spirit Hermeneutics narrates a way of reading the Bible that is faithful both to the Spirit-inspired biblical text and the experience of the Spirit among believers. -- from book flap